A large submucosal pedunculated fundal fibroid presenting as a vaginal mass: a rare case report - Priyank Singh Dasila; Maitri Shah; Pratima Thamke (MGM Journal of Medical Sciences)
This study reports the clinical outcomes of a 47-year-old female, para 1, living 1, abortion 1, with a previous lower segment cesarean section, who presented with a history of vaginal spotting and weight loss over 6 months. Both ultrasonography and magnetic resonance imaging indicated a mass originating from the lower uterus and cervix, likely of neoplastic origin. Upon vaginal and speculum examination, a soft, round cystic mass was detected, filling the vaginal cavity, making cervical evaluation impossible. However, histopathology and fluid cytology confirmed the mass as benign. An exploratory laparotomy revealed a large submucosal pedunculated fibroid originating from the fundus and extending into the vaginal cavity. The fibroid was removed, and a hysterectomy was performed. This case highlights a rare presentation of a submucosal fibroid as a vaginal mass. It underscores the importance for gynecologists to recognize this complication to avoid delays in diagnosis and prevent unnecessary morbidity and mortality.